Parenting Across Distance: Grandparent Caregiving, Child Protection, and Legal Responsibility in Indonesian Migrant Worker Families - Angga Ade Putra; Muhammad Musip (PT Taskuliah Edukasi Indonesia, 2026)
International labor migration has reshaped family structures and childcare arrangements in Indonesia, particularly through the increasing involvement of grandparents as primary caregivers for children left behind by migrant parents. This study examines childcare practices in migrant worker families in Rejang Lebong Regency, Bengkulu, and analyzes how Indonesian law responds to these arrangements. Using a socio-legal approach and qualitative case study design, the research draws on in-depth interviews with migrant parents, grandparent caregivers, and local government officials, supported by field observations and documentary analysis. Secondary data were obtained from relevant legislation, including the Marriage Law and the Child Protection Law, as well as academic literature and policy documents. The findings show that childcare is predominantly organized through delegated childcare, whereby grandparents assume daily caregiving responsibilities while parents contribute mainly through remittances and economic support. This arrangement reflects a pattern of parenting from a distance that transforms parental roles from direct caregivers into financial providers. The study further reveals a gap between legal norms and social practice. Although Indonesian law places primary responsibility for childcare on parents, informal caregiving by grandparents and other extended family members is widely accepted and socially legitimized despite receiving limited legal recognition. The study contributes to socio-legal scholarship on transnational families and underscores the need for child protection policies that better accommodate the realities of migrant worker households and evolving caregiving practices in Indonesia. [Migrasi tenaga kerja internasional telah mengubah struktur keluarga dan pola pengasuhan anak di Indonesia, terutama melalui meningkatnya peran kakek dan nenek sebagai pengasuh utama bagi anak-anak yang ditinggalkan oleh orang tua pekerja migran. Penelitian ini mengkaji praktik pengasuhan anak dalam keluarga pekerja migran di Kabupaten Rejang Lebong, Bengkulu, serta menganalisis bagaimana hukum Indonesia merespons pengaturan pengasuhan tersebut. Penelitian menggunakan pendekatan socio-legal dengan desain studi kasus kualitatif. Data diperoleh melalui wawancara mendalam dengan orang tua pekerja migran, kakek dan nenek sebagai pengasuh, serta aparat pemerintah setempat, yang didukung oleh observasi lapangan dan studi dokumentasi. Data sekunder bersumber dari peraturan perundang-undangan, khususnya Undang-Undang Perkawinan dan Undang-Undang Perlindungan Anak, serta berbagai literatur akademik dan dokumen kebijakan terkait. Hasil penelitian menunjukkan bahwa pengasuhan anak dalam keluarga pekerja migran didominasi oleh pola delegated childcare, yaitu pengalihan pengasuhan sehari-hari kepada kakek dan nenek, sementara orang tua menjalankan perannya terutama melalui dukungan ekonomi dan remitansi. Pola ini mencerminkan praktik parenting from a distance yang menggeser peran orang tua dari pengasuh langsung menjadi penyedia nafkah. Penelitian ini juga menemukan adanya kesenjangan antara norma hukum dan praktik sosial. Meskipun hukum Indonesia menempatkan tanggung jawab utama pengasuhan pada orang tua, praktik pengasuhan informal oleh keluarga besar berlangsung secara luas dan memperoleh legitimasi sosial yang kuat meskipun belum mendapatkan pengakuan hukum yang memadai. Temuan ini menegaskan pentingnya pengembangan kebijakan perlindungan anak yang lebih responsif terhadap realitas keluarga pekerja migran dan dinamika pengasuhan yang terus berkembang di Indonesia].